Elution of enteric viruses from Mississippi estuarine sediments with lecithin-supplemented eluents. - Johnson, R A (1984)
Isoelectric casein supplemented with lecithin was tested for its ability to recover enteric viruses from estuarine sediments of varied sand, silt, and clay composition. Recoveries were higher when lecithin was incorporated into an eluent as compared with trials with only the casein solution. Semipurified soybean lecithin (3%) allowed the highest overall recovery of virus from all sediments tested; crude soybean lecithin produced the lowest recovery. A difference in the percentage of virus able to be recovered from a sediment was related to the percentage of clay in the sample. Correlational statistics indicated a trend toward lower virus recovery as the clay composition of a sediment increased. Virus adsorption to the four sediments tested revealed differences between poliovirus, coxsackievirus, and echovirus adsorption that could not be explained on the basis of the clay content of a sediment.